The effect of exercise on exhaled nitric oxide depends on allergic rhinoconjunctivitis in children. (14th September 2015) - Evjenth, Bjørg; Hansen, Tonje E.; Holt, Jan
Abstract: Objective : Fractional exhaled nitric oxide (FENO ) and exercise testing are widely used for the evaluation of pediatric asthma. The evidence relating to the effects of strenuous exercise on FENO in children is conflicting. Little information is available on the association between exercise and FENO in relation to allergic rhinoconjunctivitis (AR). We aimed to investigate the effects of AR on children's FENO in response to a standardized treadmill exercise test. Methods : A total of 124 children with current asthma and 124 non-asthmatic children aged 8–16 years were studied. FENO was measured at baseline, at 1 and 30 min after an exercise challenge test using the single breath technique with EcoMedics Exhalyzer®. A structured parental interview, spirometry, serum allergen-specific IgE and skin prick tests were performed. Results : Baseline FENO was higher in both asthmatics and non-asthmatics with AR than without AR (both p < 0.001). The FENO time trend was dependent on AR ( p = 0.039), irrespective of asthma ( p = 0.876). In children with AR, FENO had declined at 1 min by a mean of 6.1 ppb with a 95% confidence level of 5.1–7.5 ppb; at 30 min, the reduction was 2.8 (2.5–3.3) ppb. In children without AR, at 1 min the decline in FENO was 2.7 (2.1–3.5) ppb and by 30 min post-exercise it was 1.6 (1.3–2.0) ppb. Conclusions : The impact of exercise on FENO was dependent on the allergic phenotype, regardless of asthma status. FENO decreased immediately after exercise, and did not return to baseline level within 30 min.